Comparison of montelukast and cabergoline for prevention of ovarian hyperstimulation syndrome: in an experimental rat model. (May 2015) - Akman, Levent; Sahin, Gulnaz; Erbas, Oytun; Aktug, Huseyin; Akdogan, Aysin; Goker, Ege Nazan Tavmergen; Taskiran, Dilek; Tavmergen, Erol
Abstract Ovarian hyperstimulation syndrome (OHSS) is a serious iatrogenic complication that can occur during assisted reproductive techniques. The aim of this study is to investigate the effects of the leukotriene receptor antagonist (montelukast) treatment in prevention of OHSS and compare to cabergoline treatment. Twenty-four immature female Wistar rats were assigned to four groups. Group 1 was the control group. In the remaning three groups, OHSS was induced through ovarian stimulation with gonadotropins. No treatment was given to Group 2. Group 3 was administered a low-dose 100 mg/kg cabergoline treatment and Group 4 was received 20 mg/kg montelukast. Body weight, ovarian weight, vasculary permability (VP), peritoneal fluid vascular endothelial growth factor (VEGF) values and VEGF immune-expression were compared between the groups. Both cabergoline and montelukast prevented progression of OHSS compared to the OHSS group. Body weight, ovarian weight, VP, peritoneal fluid VEGF values and VEGF expression were significantly lower in both cabergoline- and montelukast-treated rats than in those not treated OHSS group. In conclusion, montelukast is an effective option for prevention of OHSS, as well as cabergoline. Montelukast may be a new treatment option to prevent and control the OHSS.